Comparative evaluation of the Brucella Coombs gel test in laboratory diagnosis of human brucellosis. Issue 5 (2nd September 2016) - Koroglu, Mehmet; Aydemir, Ozlem Akkaya; Demiray, Tayfur; Erkorkmaz, Unal; Ozbek, Ahmet; Altindis, Mustafa
ABSTRACT: Brucellosis is widespread among humans and animals. Diagnosis of brucellosis mostly depends on serological methods. Serological tests are preferred over time-consuming and hazardous bacterial cultures in routine laboratory practice. However, these tests are somehow challenging due to 'incomplete/blocking antibodies' that prevent agglutination. Brucella Coombs gel test (BCGT) is newly developed test that contains Coombs antibodies (anti-human IgG) in gel microtubes and depends on gel centrifugation methods for the serological diagnosis of brucellosis. Here, performance of the BCGT is compared with standard serum tube agglutination (STA), standard serum tube agglutination with Coombs (C-STA) and immune capture agglutination (Brucellacapt). In total, 78 positive samples for study group and 16 samples for the control group were enrolled in the study. The samples were tested at dilutions of 1:40–1:5120. Titres at 1:160 and above were considered positive for brucellosis, whereas those lower than 1:160 were considered negative. Excellent agreement levels were determined between BCGT test and C-STA (κ, 0.894; p < 0.001), and BCGT and Brucellacapt (κ, 0.802; p < 0.001), when the diagnostic titre was accepted as 1:160. BCGT is easy to apply and interpret and provides reliable titre results in less than 2 h. It is also advantageous for screening.